Lots of fun at Finnegans wake : unravelling universals - Fordham, Finn (Oxford University Press, 2007)
This book is a critical introduction to Finnegans Wake and its genesis. Finn Fordham provides a survey of critical, scholarly, and theoretical approaches to Joyce's iconic masterpiece. He also analyses in detail the compositional development of certain key passages which describe the artist (Shem) and his project; the river-mother (ALP) and her "first kiss;" the Oedipal shooting of the universal father (HCE) by the priestly son (Shaun); and the bewitching and curious daughter (Issy). His analyses demonstrate 'genetic' ways of reading the text which illustrate its immense range and playfulness and how these qualities were generated in composition